THE OVERVIEW OF APPLIED METHODS FOR MEASUREMENT AND EVALUATION OF QUALITY OF ROAD TRANSPORT SERVICES - Konecny, Vladimir; Simkova, Ivana (Doprava a spoje, 2012)
The paper deals with quality of road transport services. Paper characterizes importance of quality measurement and evaluation. It includes an overview of applied methods for measurement and evaluation of quality in the field of road freight transport. Specifically it includes simple and multi-criterial evaluation methods, index methods and methods for customer satisfaction measurement.